Effective method for the detection of piroxicam in human plasma using HPLC - Adriana Maria CALVO; Mariel Tavares de Oliveira PRADO; Thiago José DIONÍSIO; Maria Paula MARQUES; Daniel Thomas BROZOSKI; Vera Lúcia LANCHOTE; Flávio Augusto Cardoso FARIA; Carlos Ferreira SANTOS (Sociedade Brasileira de Pesquisa Odontológica, 2016)
Abstract Non-steroidal anti-inflammatory drugs (NSAIDs) are widely used by the general population to alleviate inflammation and pain after oral surgeries. Piroxicam is among the most commonly used NSAIDs and excels in controlling pain, swelling, trismus and other common symptoms of inflammation. This study aimed to evaluate different concentrations of piroxicam and its major metabolite, 5'-hydroxypiroxicam, in human plasma samples over time using high performance liquid chromatography (HPLC) after liquid-liquid extraction. Briefly, 10 volunteers participated in this study after approval by the Ethics Committee of Bauru School of Dentistry, Universidade de São Paulo - USP, Brazil. Volunteers received a single dose oral of piroxicam (20 mg) and had blood collected at various times following an established protocol. The methodology of liquid-liquid extraction was effective for determining concentrations of piroxicam in plasma using HPLC in 10 out of 10 volunteers while 5'-hydroxypiroxicam was only detected in 2 out of 10 volunteers.